A inserção de acadêmicos e licenciados do curso de Pedagogia da Universidade Federal de Sergipe no campo educacional sergipano (1968-1978) - Oliveira, Nayara Alves de (2017)
The major purpose of this dissertation is to analyse the insertion and practice of students and graduates on Pedagogy of the Universidade Federal de Sergipe (1968-1978) in the educational field in Sergipe. Another goal is to comprehend the opening of this academic field and its functioning and legitimation in the local sphere, and its contribution to the formation of teachers and Education specialists. For which it was donne a historical research based on bibliographic and documental analyses, both on the framework of the New History theoretical and methodological premises, more precisely of the new historiographic school named Cultural History. Besides, the study was oriented by the concept of field, capital and habitus, on Bourdieu’s account, and the concept of memory on Le Goff’s and Pollak’s account. According to the research, it is possible to conclude that the graduation on Pedagogy was among the courses authorized to be offered by the Faculdade Católica de Filosofia de Sergipe (FAFI), from 1951. However, the course had only been given to the public on 1968 after the inauguration of the Universidade Federal de Sergipe in 1967. The graduation course was opened by a determination of the civilmilitary government in order to inaugurate the Universidade Federal de Sergipe which required the FAFI’s fragmentation and the implementation of the Institute of Languages, Philosophy and Human Sciences and the Faculty of Education. After its implementation it was the most popular graduation course during the decades of 1960 and 1970 on the field of Education in the Universidade Federal de Sergipe. One of the reasons for it is associated to the national reformulation in 1969, which included the broadening of the field of expertise for educators by creating the habilitations: coordination, administration, supervision, and school inspection. Educators and specialists had worked in strategic functions of the educational field in this process, contributing to the modernization and expansion of teaching. In this sense, it is not possible to omit or deny the students’ and graduates’ contributions in the implementation of educational polices on the improvement of teaching, despite the fact that the course was implemented after an imposition of the civil-military government, and of the dominant interpretation of social and ideologic control as the main interest of the government.